Driven by FOMO: how the fear of missing out shapes information-seeking behaviors in university students - Muhammad Rifky Nurpratama (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2026)
This study examines the relationship between the Fear of Missing Out (FOMO) and information-seeking behavior among undergraduate students in the Faculty of Humanities, Universitas Diponegoro. Grounded in Self-Determination Theory and the Information Search Process model, the study explores how unmet psychological needs influence students’ motivations to seek information. A quantitative research design was employed using a structured questionnaire for 364 students selected through simple random sampling. Data were analyzed using simple linear regression with SPSS software. The analysis revealed a strong positive correlation between FOMO and information-seeking behavior, explaining 68.4% of the variance. Students with higher FOMO levels demonstrated more frequent and intensive information-seeking activities, indicating that FOMO serves as an emotional and psychological driver. The study concludes that FOMO significantly influences students’ information-seeking behavior. These findings provide practical implications for university administrators in helping students develop healthier information-seeking strategies. Further longitudinal research is recommended to establish causal relationships and explore how digital platform interactions shape these behaviors over time